PENYELESAIAN SENGKETA AKIBAT KEADAAN MEMAKSA (FORCE MAJEURE) PADA PERJANJIAN KEPEMILIKAN RUMAH ANTARA PENGEMBANG DENGAN KONSUMENNYA (Studi Pada PT. Revalindo Cipta Mandiri) - Sugarman, Wan (UNES Law Review, 2020)
As stipulated in Law Number 1 of 2011 concerning Housing and Settlement Areas, the state is responsible for protecting the entire Indonesian nation through the implementation of housing and settlement areas so that people, especially low-income people, can live and inhabit decent and affordable houses inside. a healthy, safe, harmonious and sustainable environment throughout Indonesia. In order to fulfill the housing administration, the government also expects community self-sufficiency through developer companies. This research is a descriptive analytical study, with a normative juridical approach as the main approach and empirical juridical as a support. The data used are secondary data and primary data collected through library research and field studies with interview techniques. The analysis was carried out qualitatively and presented in a qualitative descriptive form. Based on the results of the research that has been analyzed, it can be concluded that, first, the developer will attempt to resolve disputes with consumers caused by force majeure by means of peaceful negotiations. Second, before the peace negotiations are carried out, the developer will prepare a negotiation strategy such as taking inventory of potential disputes. Third, prepare a dispute resolution mechanism so that it is hoped that it can be resolved peacefully and amicably. Fourth, the developer of PT. Revalindo Cipta Mandiri will continue to build the Griya Dwitama Housing which was abandoned due to the earthquake, because the developer has spent little capital to start the housing development.